Penerapan metode Tartil dalam meningkatkan keterampilan bahasa Arab santri di Ponpes Al-Fatah Sukabumi: Implementation of the Tartil Method in Enhancing Arabic Language Skills of Students at Al-Fatah Islamic Boarding School, Sukabumi - Robiatussadiah, Siti; Komarudin, Komarudin; Nurfalah, Muhammad Syamsudin; Nurmiati, Ai Siti; Rustandi, Nandi (Risalah Kharisma, 2024)
The ability to speak Arabic (maharah al-kalam) is essential for students in Islamic boarding schools, especially in learning the Qur'an and other Arabic texts. However, many students struggle with reading the Qur'an fluently and understanding Arabic structure. This indicates the need for an effective and integrated learning method. This study aims to assess the effectiveness of the tartil method in improving the Arabic speaking skills of students at Pondok Pesantren Al-Fatah Sukabumi. A qualitative descriptive approach was employed, involving 15 participants. Data were gathered through observation, interviews, and oral tests. The results show that the tartil method, when applied systematically, positively impacted the students' pronunciation, fluency, and understanding of Arabic in the Qur'anic context. Group practice and direct interaction with the Qur'an enhanced students' confidence and ability to speak Arabic in religious settings. The findings suggest that the tartil method can be an effective tool in Arabic language learning at pesantren, integrating tajwid knowledge and language skills. The study also highlights the importance of independent practice time in improving Arabic proficiency.